Nucleotide variation in the triosephosphate isomerase (Tpi) locus of Drosophila melanogaster and Drosophila simulans. - Hasson, E.; Wang, I.N.; Zeng, L.W.; Kreitman, M.; Eanes, W.F. (Molecular Biology and Evolution, 1998)
DNA sequence variation in a 1.1-kb region including the coding portion of the Tpi locus was examined in 25 homozygous third-chromosome lines of Drosophila melanogaster, nine lines of Drosophila simulans, and one line of Drosophila yakuba. Our data show that the widespread allozyme polymorphism observed in cosmopolitan D. melanogaster is due to a glutamic acid substitution occurring in a phylogenetically conserved lysine that has been identified as part of the "hinged-lid" active site of the enzyme. This observation suggests that the replacement polymorphism may have important functional consequences. One replacement polymorphism was also observed in D. simulans, although its functional relevance is more difficult to assess, since it affects a site that is not strongly conserved. This amino acid change in D. simulans is associated with a single lineage possessing seven unique silent substitutions, which may be indicative of balancing selection or population subdivision. The absence of fixed amino acid differences between D. melanogaster and D. simulans and only a single difference with D. yakuba suggests that triose phosphate isomerase is under strong functional constraint. Silent variation is slightly higher for D. melanogaster than for D. simulans. Finally, we outline the general lack of evidence for old balanced polymorphisms at allozyme loci in D. melanogaster.